Positive psychology interventions in golf: Mindfulness versus positive self-talk (Frontiers in Psychology, 2015)
Aims: Methods that optimise athletic performance have long been of interest in the field of applied sport psychology. However, recent research has questioned traditional psychological skills training due to a lack of consistency in previous research, and empirical support for alternatives such as mindfulness training. Testing differences between mindfulness and a traditional psychological training tool, positive self-talk, in enhancing performance of golfers, was the focus of the current study. Method: Fifty-eight adult golfers were randomly assigned to one of three groups; self-guided mindfulness training (n=22), positive self-talk (n=17), or a control group (n=19). The prescribed protocols included pre-round practice and brief use before each golf shot over 4 weeks. Pre- and post-intervention data on golf handicap, on the Kentucky Inventory of Mindfulness Skills (KIMS) and putting test performance were analysed. Frequency of play and self-reported adherence to the protocol were also assessed. Results: There was a significant multivariate effect of Time on putting test scores, F(1, 21) = 13.9, p = .001, Ƞ2 = .399. Specifically, a mean increase of 1.4 out of 10 putts over the 4-week intervention period was found, but no univariate effect of Time on distance (cm) from the hole for putts missed. There was no Group or Time by Group interaction effect for either putting test variable. Furthermore, groups did not differ at baseline or post-intervention on reported handicap, KIMS, technique adherence, or rounds of golf played. Conclusions: These preliminary findings fail to support previously reported findings that mindfulness or positive self-talk have short-term effects on putting accuracy. To maximise access, the current study used a self-guided intervention, which may have accounted for the lack of improvement that may occur with one-on-one coaching.